Off-Label Medicines Use: Complex Problem of Modern Clinical Practice - S. R. Gilyarevskiy (Столичная издательская компания, 2020)
World experience in off-label medicines use is presented in the article. Data on the history of changes in tactics and approaches to solve the problem of medicines off-label use in the USA and some European countries, as well as in the European Union as a whole, are presented. The reasons, why doctors should use medicines off-label, are discussed. The expert opinion on the conditions ensuring the maximum safety in off-label medicines use is presented. In particular, the validity of obtaining patient informed consent is discussed. The article does not apply to the Russian regulation regarding "off-label" therapy but describes the foreign practice related to off-label medicines use. In addition, the results of some recently completed randomized clinical trials evaluating the effects of direct oral anticoagulants are presented in order to demonstrate the need to clarify the effectiveness and safety of medicines used in certain clinical situations. The results of such studies clarify the indications for the drug use, which are subsequently entered into the summary of product characteristics.